Outcomes from the Northeast England cohort of autosomal dominant polycystic kidney disease (ADPKD) patients on tolvaptan - Gkekas, Eleftherios; Tang, Tsz Yau Tiffany; Green, Alan; Davidson, Han; Fraser, Rachel; Sayer, John A.; Srivastava, Shalabh (Frontiers in Nephrology, 2022)
Autosomal dominant polycystic kidney disease (ADPKD) is a cause of end-stage kidney disease (ESKD). The vasopressin V2-receptor antagonist tolvaptan has been shown within randomised clinical trials to slow down decline of kidney function in patients with ADPKD at risk of rapid progression. We performed a retrospective review of a Northeast England cohort of adult ADPKD patients who had been established on tolvaptan therapy to determine its efficacy in a real-world clinic setting. Other inclusion criteria involved a pre-treatment decline in greater than 2.5 ml/min/1.73m2/year based on readings for a 3 year period, and ability to tolerate and maintain tolvaptan treatment for at least 12 months. We calculated based on eGFR slopes, predicted time to reach ESKD with and without tolvaptan therapy. The cohort of patients included 21 from the Northeast of England. The mean rate of eGFR decline prior to treatment was -6.02 ml/min/1.73m2/year for the cohort. Following tolvaptan treatment, the average decline in eGFR was reduced to -2.47 ml/min/1.73m2/year, gaining a mean 8 years and 4 months delay to reach ESKD The majority of patients (n=19) received and tolerated full dose tolvaptan (90 mg/30 mg). The real-life use of tolvaptan gave a dramatic improvement in eGFR slopes, much more than previously reported in clinical studies. These effects may be in part due to careful patient selection, selection and inclusion of patients who were able to tolerate tolvaptan therapy, excellent compliance with medication and a “tolvaptan clinic” effect where great personal care was given to these patients.